A Discussion of Virtual Reality As a New Tool for Training Healthcare Professionals - Fertleman, Caroline; Aubugeau-Williams, Phoebe; Sher, Carmel; Lim, Ai-Nee; Lumley, Sophie; Delacroix, Sylvie; Pan, Xueni (Frontiers in Public Health, 2018)
Background Virtual reality technology is an exciting and emerging field with vast applications. Our study sets out the viewpoint that virtual reality software could be a new focus of direction in the development of training tools in medical education. We carried out a panel discussion at the Center for Behavior Change 3rd Annual Conference, prompted by the study, “The Responses of Medical General Practitioners to Unreasonable Patient Demand for Antibiotics––A Study of Medical Ethics Using Immersive Virtual Reality” (1). Methods In Pan et al.’s study, 21 general practitioners (GPs) and GP trainees took part in a videoed, 15-min virtual reality scenario involving unnecessary patient demands for antibiotics. This paper was discussed in-depth at the Center for Behavior Change 3rd Annual Conference; the content of this paper is a culmination of findings and feedback from the panel discussion. The experts involved have backgrounds in virtual reality, general practice, medicines management, medical education and training, ethics, and philosophy. Viewpoint Virtual reality is an unexplored methodology to instigate positive behavioral change among clinicians where other methods have been unsuccessful, such as antimicrobial stewardship. There are several arguments in favor of use of virtual reality in medical education: it can be used for “difficult to simulate” scenarios and to standardize a scenario, for example, for use in exams. However, there are limitations to its usefulness because of the cost implications and the lack of evidence that it results in demonstrable behavior change.